Inequalities of aging : paradoxes of independence in American home care - Buch, Elana D. (Anthropologies of American medicine., 2018)
"Elana D. Buch's "Inequalities of Aging: Paradoxes of Independence in American Home Care" focuses on the topic of American home care and explores various contradictions and points of tension within the industry. It also raises awareness of the problematic inequality that exists in the American home care industry and argues for the creation of a more sustainable system."--